Міжнародно-правовий статус Комітету ООН з прав людини - Зубарева, Антоніна Євгенівна; Зубарева, Антонина Евгеньевна; Zubareva, Antonina Y. (Одеса, 2015)
У дисертації досліджено зміст міжнародно-правового статусу Комітету ООН з прав людини. Розглянуто юридичні підстави діяльності Комітету, проведено їх класифікацію. Проаналізовано історичну ретроспективу створення та діяльності Комітету, основні підходи до його місця в системі міжнародного співробітництва в сфері захисту прав людини на різних етапах. Досліджено внутрішньо-організаційний механізм Комітету, основні правові засади його функціонування. Особливу увагу приділено компетенції Комітету, вивченню функцій та повноважень цього міжнародного органу, процедури його діяльності. Вивчено проблеми реалізації повноважень Комітету з розгляду доповідей держав-учасниць Міжнародного Пакту про громадянські та політичні права 1966 р., індивідуальних повідомлень про порушення та міждержавних спорів, а також переваги та недоліки поточної процедури діяльності Комітету. Встановлено, що за юридичною природою рішення Комітету можна вважати «актами м’якого права» нарівні з рішеннями міжнародних організацій. Проаналізовано організаційно-правові засади взаємовідносин Комітету з іншими суб’єктами міжнародного співробітництва із захисту прав людини. Запропоновано шляхи розв’язання проблемних питань співпраці між Україною та Комітетом.

В диссертации исследовано содержание международно-правового статуса Комитета ООН по правам человека. Рассмотрены юридические основания деятельности Комитета, их классификация. Проанализирована историческая ретроспектива создания и деятельности Комитета, основные подходы к определению его места в системе международного сотрудничества в области прав человека на разных этапах. Исследовано внутриорганизационный механизм Комитета, основные правовые принципы его функционирования. Особое внимание обращено на компетенцию Комитета, изучены функции и полномочия этого международного органа, процедуры его деятельности. Проанализированы проблемы реализации полномочий Комитета по рассмотрению докладов государств-участников Международного Пакта о гражданских и политических правах 1966 г., индивидуальных сообщений о нарушениях и межгосударственных споров, а также преимущества и недостатки текущей процедуры деятельности Комитета. Установлено, что по своей юридической природе решения Комитета можно считать «актами мягкого права» наряду с решениями международных организаций. Проанализированы организационно-правовые основы взаимоотношений Комитета с другими субъектами международного сотрудничества по защите прав человека. Предложены способы решения проблемных вопросов сотрудничества между Украиной и Комитетом.

This dissertation reviews the contents of the international legal status of the UN Human Rights Committee. The first Chapter starts with the analysis of the historical background formation and development of the establishment and functioning of UN Human Rights Committee. Main stages of the development of this process are pointed out. Special attention is paid to the United Nations role in this process. Further, the legal grounds of the UN Human Rights Committee functioning are considered. The sources of regulation of the Committee’s legal status are characterized. It is emphasized that the International Covenant on Civil and Political Rights of 1966 is the main source of the Committee’s international legal status. The classification of the sources as main and additional is conducted. Particular attention is paid to the intra-organizational mechanism of the Committee. The role of the different elements of this mechanism is compared. The conclusions about the possible directions of the reforming of the Committee’s intra-organizational mechanism are made. In the Chapter II the issues of UN Human Rights Committee’s competence, functions and powers are analyzed. The four main functions of the Committee are pointed out and compared with the functions of other UN treaty Committees. It is concluded that the consideration of reports of ICCPR States parties is the main power of the Committee. The power of Committee to consider the interstate disputes is studied. The main principles of the consideration of the individual claims by the Committee are viewed and the effectiveness of this procedure is estimated. The conclusions about the legal nature of the Committee’s decisions as a soft law are made. The last Chapter deals with the relations between the Committee and other participants of the international legal cooperation concerning the human rights protection. The Committee’s procedures are studied and their effectiveness, including strong and weak sides, is estimated. The legal basis of this cooperation, especially with other UN treaty bodies, is analyzed. Main problems of the relations between Ukraine and UN Human Rights Committee are defined. The possible ways of solving of these problems of Ukraine-UN Human Rights Committee are formulated. It is concluded that the further development of the international cooperation between Ukraine and Committee can be solves by the amendments to the legislation of Ukraine.
дис. ... к.ю.н. : 12.00.11
Зубарева А. Є. Міжнародно-правовий статус Комітету ООН з прав людини : дис. ... к.ю.н. : 12.00.11 / Зубарева Антоніна Євгенівна. - Одеса, 2015. - 211 арк.
Keywords: інституційний механізм захисту прав людини; Комітет ООН з прав людини; правовий статус міжнародної організації; права людини; рішення міжнародних органів та організацій; міжнародна судова процедура; институциональный механизм защиты прав человека; Комитет ООН по правам человека; правовой статус международной организации; права человека; решения международных органов и организаций; международная судебная процедура; institutional mechanism of human rights’ protection; UN Human Rights Committee; legal status of international organization; human rights; the decisions of international organizations; international judicial procedure